Estudo morfofisiológico dos efeitos do flavonoide crisina sobre o desenvolvimento pré-puberal da próstata de gerbilos (meriones unguiculatus) - Ribeiro, Naiara Cristina de Souza (2017)
The prostate is a gland of the male reproductive system accessory, but not exclusively of males, and can be found in females of various mammals. Changes in hormone metabolism mediated by exogenous substances can interfere with the activity of this gland. An example is chrysin (5,7-dihydroflavone), a natural compound found in plants. This substance modulates the action of sex hormones, interfering with the synthesis and metabolism of steroid hormones. The objective of this study was to evaluate the effects of exposure to chrysin on the prepubertal development of the prostate of gerbils of both sexes. Thirty males and 30 females of adult gerbils were used. Each of these females was maintained with a male of the same age for mating to occur. After the cubs were born, three experimental groups were formed: 1) Control (dilution vehicle); 2) chrysin (25 mg/kg/day); 3) Positive Control (1 mg/kg/week testosterone cypionate). Males and females of all groups were treated from the 15th to the 42nd postnatal life and euthanized on the 43rd day (onset of puberty) and 90 days (onset adult). The organs were submitted to morphological, stereological and Immunohistochemical analysis. The results showed that pre-pubertal exposure to chrysin did not alter the structural parameters of the prostate of pubertal gerbils, thus increasing the frequency of androgenic (AR) and alpha estrogen (ERα) receptors. Testosterone promoted an increase in the volume and secretory activity of the alveoli at this stage of development. In male and female adult animals, chrysin promoted an increase of secretory epithelium presenting highly developed prostate glands, with a high rate of cell proliferation and high secretory activity. In addition, it maintained a significant increase in the rate of cell proliferation and the frequency of AR, and ERα-positive cells. The results allowed to conclude that the pre-pubertal exposure to chrysin caused permanent changes in development, which only became noticeable in adult life. Studies indicate that pre-pubertal exposure to flavonoid chrysin causes hormonal disorders that are capable of permanently altering prostate homeostasis. Since the high consumption of these flavonoids during the developmental stages one must be more careful since chrysin permanently changes the mofophisiology of hormone-dependent organs.